Factor Related to The Incidence of Ascites in Chronic Kidney Disease Patients Undergoing Hemodialysis at RSUD Dr Moewardi Surakarta: A Cross Sectional Study - Felizia Alika Yusman; Ratih Tri Kusuma Dewi; Yusuf Ari Mashuri; Evi Nurhayatun (Jurnal Penyakit Dalam Indonesia)
Introduction. Chronic kidney disease (CKD) is a global health issue with continuously rising prevalence. Fluid overload is a frequent systemic complication which occurs in CKD patients undergoing hemodialysis (HD). One of clinical manifestation of fluid overload in HD patients is ascites. This study aimed to determine the factors related to the incidence of ascites in CKD patients undergoing hemodialysis.